Factors associated with personal and professional beliefs about vaccines: a cross-sectional study of national dental practice-based research dentists - David M. Mosen; Jeffrey L. Fellows; Mary Ann McBurnie; Ning Smith; Michael C. Leo; Phillip Crawford; Veerasathpurush Allareddy; Inga Gruß; Dea Papajorgji-Taylor; Gregg H. Gilbert (Frontiers in Oral Health, 2026)
Introduction Our study examined associations between dentists' demographic and practice characteristics and their personal and professional beliefs about vaccines, vaccine delivery and recommendations to influence patient vaccination. Methods A cross-sectional survey of 537 dentists in the National Dental Practice Based Research Network. Personal beliefs were assessed using the 5C Scale of Vaccine Hesitancy; professional beliefs were based on dentists' perceived role in recommending and delivering vaccines. Factor analysis was used to construct three outcome measures: 1) personal beliefs about vaccines, 2) professional beliefs about vaccine delivery and 3) professional beliefs about the efficacy of dentist recommendations to influence patient vaccination. Results Regarding personal beliefs, dentists' age (55–64) was associated with higher support for vaccines; dentists' Hispanic ethnicity was associated with lower support; and a private practice, group setting or dental school was associated with higher support than a private practice, solo setting. Regarding professional beliefs, dentists' African-American race was associated with more positive beliefs about vaccine delivery and provider recommendations to influence vaccination. Dentists in dental school and public health settings had higher positive beliefs regarding vaccine delivery; those in rural locations had lower positive beliefs. Dentists treating children and adults reported lower positive beliefs about provider recommendations. Higher personal support for vaccines predicted more positive scores on both professional belief measures. Discussion We identified factors associated with dentists' personal and professional beliefs about vaccines. Future research should assess whether interventions to change dentists' personal beliefs about vaccines also result in changes in professional beliefs and patient vaccination.